From Island Biogeography to Conservation: A Multi-Taxon and Multi-Taxonomic Rank Approach in the Tuscan Archipelago - Enrico Ruzzier; Leonardo Forbicioni; Rodolfo Gentili; Nicola Tormen; Olivia Dondina; Valerio Orioli; Luciano Bani (Land, 2021)
Investigating the drivers that support species richness (S) in insular contexts can give insights for the conservation of insular biodiversity. Our aim was to decouple the effect of drivers (island area, distance from mainland and habitat diversity) accounted in three hypotheses or a combination of them in explaining S in seven islands of the Tuscan Archipelago: Area (species–area relationship, SAR), area and distance from mainland (equilibrium hypothesis, EQH) and habitat (habitat diversity hypothesis, HDH). We used published and original datasets to assess S (except aliens) for 42 taxa (14 animal and 28 plant taxa) in each island, and we used S as the dependent variable and the drivers as covariates in regression models. In 31 taxa, the data supported one of the tested hypotheses or a combination of them, and the most commonly supported hypotheses were SAR (12 taxa) and EQH (10 taxa). The effect of the area was also evident in SAR + HDH (five taxa) and EQH + HDH (one taxon), making it the prevailing driver in explaining S. Since distances are relatively short, and three out of four islands are land-bridge islands, the effect of distance was significant for 12 taxa. The effects of habitat diversity were evident for just nine taxa. The multi-taxon approach allowed us to understand the differential effect of drivers among taxa in influencing S in a single archipelago. Moreover, the multi-taxonomic rank approach highlighted how the information contained within higher taxonomic ranks (e.g., Division) can be substantially different from that derived from lower ranks (e.g., Family). These insights are of particular importance from a conservation perspective of the archipelago’s biodiversity, and this approach can be transferred to mainland fragmented systems.